Two new species of Riethia Kieffer, 1917 from Chile and Ecuador (Chironomidae: Chironominae, Pseudochironomini) - Andersen, Trond; Sanz-Laparra, Annui Malla; Giłka, Wojciech (Zootaxa, 2024)
Two new species of Riethia Kieffer, 1917, R. chilensis sp. nov. (Chile) and R. ecuadoriensis sp. nov. (Ecuador) are described and figured as adult males. The two species differ from the presumable closest relative, R. truncatocaudata (Edwards, 1931), by uniformly coloured legs, without bands, and stout curved hypopygial superior volsellae; they can be separated from all other Riethia by the shape and setation pattern of the inferior volsella. The two new species differ from each other in body colouration, including abdomen, and in the presence/absence of microtrichia on superior volsellae.